Faktor - faktor Penyebab Rendahnya Minat Melanjutkan ke Perguruan Tinggi di SMK Miftahul Ulum Cimerak - Neneng Nurmalasari; Taopik Hidayat; Imron Rosadi; Rika Yunita; Elis Holisoh (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
This research is entitled, "Factors Causing Low Interest in Continuing Education to Higher Education". The purpose of this research is to examine what factors cause low interest in continuing education to tertiary institutions (universities) at SMK Miftahul Ulum Cimerak. This research uses qualitative research with descriptive type, collection technique with triagulation (combined), data analysis is inductive/qualitative, and taking informants by purposive sampling with a total of 44 informants. The data source for this research was a questionnaire filled in by students at SMK Miftahul Ulum Cimerak. The results of this study are (1) the internal factors that cause low interest in continuing their education to tertiary institutions are the lack of motivation or desire to go to college and the desire to find work independently. (2) External factors that cause low interest in continuing education to tertiary institutions are economic limitations or expensive tuition fees and social environmental factors.